Enhancing Operating Rules for Water Pumping Stations Under Transient Flow Conditions by Using Surge Tanks - Abdulameer, Layth; Shemal, Khalid; Al-Maimuri, Najah M. L.; Al-Khafaji, Mahmoud Saleh; Al-Dujaili, Ahmed N.; Rashid, Farhan Lafta (Salehan Institute of Higher Education, 2025)
With an emphasis on Pump Station 1 (PS1) of the Basra Water Project (Open Canal) in Iraq, this study examines the essential hydraulic parameters of water pumping stations under transient flow situations. The study assesses the effects of routine operations, unexpected shutdowns, and surge tank installations on pressure stability and system flexibility using hydraulic modeling with HAMMER V8i. The findings show notable changes in pressure during brief occurrences. An abrupt shutdown without surge tank protection resulted in minimum pressures of 12.5 m in pipes L1 and L2, exposing them to hydraulic transient effects. The maximum pipe pressure under normal circumstances was 17.5 m (L3). Because of its exposure to low-pressure occurrences, the analysis identifies L1 as the most in-danger pipeline. It has been demonstrated that traditional operating procedures, which frequently ignore transient dynamics, increase the probability of service disruption and lead to inefficiency. In contrast, adding surge tanks reduces pressure variability and lessens the impacts of the water hammer, significantly increasing pressure stability, especially when three tanks are used. The results highlight how adaptable operational procedures are essential for employing and managing water delivery systems. According to the study findings, adding surge tanks improves durability and performance while lowering the risks of transient flow occurrences. This offers a guide for restructuring water pumping station operations.